Ocular blood flow in glaucoma – the Leuven Eye Study - Abegão Pinto, Luís; Willekens, Koen; Van Keer, Karel; Shibesh, Abraham; Molenberghs, Geert; Vandewalle, Evelien; Stalmans, Ingeborg (Acta ophthalmologica (Oxford, England), 2016)
Purpose Elevated intra‐ocular pressure (IOP) has been identified as a major risk factor for glaucoma. Additionally, extensive literature depicts a vascular dysfunction to exist in these patients. However, a large ocular blood flow‐oriented trial to integrate these findings in the clinical setting is lacking. This study would likely help to identify which of these vascular data can be used as a clinical tool for screening and disease stratification. Method Prospective, cross‐sectional, case–control hospital‐based study. Patients with primary open‐angle glaucoma (POAG), normal‐tension glaucoma (NTG), ocular hypertension (OHT), glaucoma suspects and healthy volunteers were recruited. In addition to a comprehensive ophthalmological examination, a vascular‐oriented questionnaire was completed and ocular blood flow assessment (colour Doppler imaging of retrobulbar vessels, retinal oximetry, dynamic contour tonometry, optical coherent tomography enhanced‐depth imaging of the choroid) were performed. Statistical analysis was based on multiple imputation to account for missingness. Results A total of 614 subjects (291 males) were recruited between March and December 2013 (POAG: 214, NTG: 192; OHT: 27; glaucoma suspect: 41; healthy controls: 140). Glaucoma groups (NTG and POAG) were age and gender matched with the control group (p > 0.05). Glaucoma groups were paired in terms of functional and structural parameters (p > 0.08). Mean ocular perfusion pressure was higher in the glaucoma groups than in controls (p < 0.001). Glaucoma groups had lower retrobulbar velocities, higher retinal venous saturation and choroidal thickness asymmetries when compared to the healthy group, in line with the current literature. Conclusions The Leuven Eye Study stands as one of the largest clinical trials on ocular blood flow in glaucoma. The creation of this vast database may help integrate the vascular aspects of glaucoma into the clinical practice of glaucoma.